Building the evidence base for dengue vector control: searching for certainty in an uncertain world - Horstick, Olaf; Boyce, Ross; Runge-Ranzinger, Silvia (Pathogens and global health, 2018)
This review discusses biological and chemical methods for dengue vector control, using recently emerging summary evidence, meta-analyses and systematic reviews to conclude on practical public health recommendations for Aedes control, which is increasingly relevant in an era of widespread Chikungunya, yellow feer and Zika outbreaks.The analysis follows an a priori framework of systematic reviews by the authors on vector control methods, distinguishing vector control methods into biological, chemical and environmental methods. Findings of each published systematic review by the authors, following each individual vector control method, are summarised and compared in the discussion against the findings of existing meta-analyses covering all vector control methods.Analysing nine systematic reviews and comparing to two existing meta-analyses provided low-to-moderate evidence that the control of Aedes mosquitoes can be achieved using 1) chemical methods, particularly indoor residual spraying and insecticide treated materials, and 2) biological methods, where appropriate. The level of efficacy and community effectiveness of the methods in most studies analysed is low, as was the overall assessment of study quality. Furthermore, the results show that too optimise results, larvae and adults should be targeted simultaneously. The quality of service delivery is probably one of the most important features of this analysis - and including high coverage.The analysis also highlights the urgent need for standards to guide the design and reporting of vector control studies, ensuring the validity and comparability of results. These studies should aim to include measurements of human transmission data - where and when possible.
Gesehen am 15.08.2019